Economic Feasibility of Biofuel Crops in Florida: Energycane on Mineral Soils - José Alvarez; Zane R. Helsel (EDIS)
Energycane is a cross of commercial sugarcane with wild sugarcane. It is higher in fiber and lower in sucrose than commercial sugarcane. This 7-page fact sheet provides estimates of costs and returns to sugarcane farmers and determines whether energycane can provide sufficient economic returns to warrant further research into its use as an energy crop. Written by José Álvarez and Zane R. Helsel and published by the UF Department of Food and Resource Economics, August 2011. USDA/ARS photo by David Nance.